2015
DOI: 10.1371/journal.pone.0134634
|View full text |Cite|
|
Sign up to set email alerts
|

Eliminating Anti-Nutritional Plant Food Proteins: The Case of Seed Protease Inhibitors in Pea

Abstract: Several classes of seed proteins limit the utilisation of plant proteins in human and farm animal diets, while plant foods have much to offer to the sustainable intensification of food/feed production and to human health. Reduction or removal of these proteins could greatly enhance seed protein quality and various strategies have been used to try to achieve this with limited success. We investigated whether seed protease inhibitor mutations could be exploited to enhance seed quality, availing of induced mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…Trypsin/chymotrypsin inhibitors (TIs) are another class of proteins that affect digestibility (Clemente et al . ) and are covered in more detail below in the section on anti‐nutrients.…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypsin/chymotrypsin inhibitors (TIs) are another class of proteins that affect digestibility (Clemente et al . ) and are covered in more detail below in the section on anti‐nutrients.…”
Section: Proteinmentioning
confidence: 99%
“…) and digestion of protein (Clemente et al . ). Genetic breeding could help to optimise beneficial nutrients while reducing the levels of anti‐nutrients in pulse seeds.…”
Section: Introductionmentioning
confidence: 97%
“…Crucially, it was demonstrated that a double null TILLING mutant of Pisum elatius could be successfully introgressed into P . sativum breeding lines, highlighting the importance of land races and wild cultivars, as well as the potential for such approaches to be adopted in other crop species (Clemente et al, ).…”
Section: The Benefit Of Legumesmentioning
confidence: 99%
“…Additionally, the introgression of a P . elatius accession to reduce seed coat BBI content in agricultural P. sativum lines is described above (Clemente et al, ). However, rewilding also has the potential to introduce potentially detrimental genetic elements into breeding programs.…”
Section: Legume Biofortificationmentioning
confidence: 99%
“…The adverse health effects have been detected in experimental animals and it can be seen that occurred pancreatic hypertrophy, decreased growth and weight reduction in animals (Grela, 1996;Clemente et al, 2015).…”
Section: Introductionmentioning
confidence: 99%